"A Community with Diversity of Culture, Wealth, Resources, and Living Experiences": Defining Neighborhood in an Unincorporated Community. Issue 1 (23rd January 2014) - Fernández, Jesica Siham; Langhout, Regina Day
Abstract: To obtain a better understanding of how people living in an unincorporated region define their neighborhood, a long‐term photovoice project was conducted. Thirty‐one photovoice sessions and eight structured interviews were coded and analyzed to assess participants' neighborhood definitions. Participant's difficulties in identifying the geographic, physical and demographic characteristics of their neighborhood led them to use social interactions, place‐mediated values, and civic engagement to define neighborhood.